Application of Synthetic Nanozeolite Sodalite in Drug Delivery - Rahmani, Shaghayegh; Azizi, Seyed Naser; Asemi, Neda (International Current Pharmaceutical Journal, 2016)
In this study nanozeolite sodalite was synthesized from natural volcanic glass (perlite) as silica (Si) source and sodium aluminate as aluminium (Al) source without using any organic template. We use perlite as Si source because it is cost-effective and available source. These nanoparticles of synthesized zeolite were prepared at 170°C in stainless steel reactor with hydrothermal method. The synthesized nanozeolite was characterized by X-ray diffraction (XRD), fourier transform infrared (FTIR) and scanning electron microscopy (SEM) techniques. Chemical composition of perlite was determined by X-ray fluorescence (XRF).This nanozeolite was modified with cationic surfactant, hexadecyltrimethylammonium bromide (HDTMAB). In this study adsorption of cetirizine (Cet) as a model drug onto nanozeolite sodalite as a carrier of drug was investigated and Ultra Violet-Visible (UV-Vis) spectrophotometry was used for determination of concentrations of Cet at 230 nm. Adsorption characteristics of Cet on nanozeolite sodalite were examined at different times (0-6 h) and also the analysis was carried at three pH levels 4, 5 and 6. Finally three buffered solutions with different pH (1.2, 6.8 and 7.2) were selected for release medium and the temperature was precisely controlled at 37 ± 0.1°C. Rahmani et al., International Current Pharmaceutical Journal, May 2016, 5(6): 55-58